Drawing as Language in Panoramic Sketches Created During the Spanish Civil War (diségno, 2025)
The article focuses on the analysis of panoramic sketches drawn during the Spanish Civil War in Aragón. These sketches are perspective drawings that depict the warfront landscape as perceived by combatants from strategic positions on both sides of the contact line.They are elongated graphic documents, generally of large dimensions, created by specialists integrated into the participating Spanish and Italian troops.These sketches are part of the cartographic material necessary for the meticulous study of the terrain where military actions took place. The prolonged stagnation of the front in Aragón allowed for precise delineation of the relief profiles and the placement of positions, trenches, and fortifications. The sketches served as a means of communication between the message sender, the draftsman, and the receiver, who projected operations onto the territory.The technical quality of the documents and the validity of the transmitted message are evaluated. The authors’ ability to express the complexity of the territory through the language of drawing is assessed. The phases of their creation and their characteristics are investigated. Additionally, the calculation procedures, graphic techniques used, and methods available for obtaining duplicates are analyzed.
Keywords: landscape; graphic expression; Spanish Civil War; territory; chorographies